Reappraisal of Dendroceros cucullatus (Dendrocerotaceae, Anthocerotophyta) - Chantanaorrapint, Sahut; Peng, Tao; Zhu, Rui-Liang (Phytotaxa, 2014)
Dendroceros is an epiphytic or epiphyllous genus within Anthocerotophyta, with about 48 extremely specialised species in having endosporic germination (Villarreal et al. 2010; Garcia et al. 2012). Dendroceros difficilis was originally described by Stephani (1917: 1009), based on a collection made by V. Schiffner from Java, Indonesia. Hasegawa (1980) reduced a little-known species D. cucullatus Stephani (1923: 429) from the Philippines, to its synonym. An examination of the holotypes of both species, however, reveals that D. cucullatus is quite different from D. difficilis in thallus margin, structure of costa and epidermal cells of capsule. Dendroceros cucullatus is thus reinstated as a separate species. Based on Schuster’s (1987) treatment, these two species belong to subgenus Apoceros Schuster (1987: 195) based on the cavernous costa in both. Dendroceros difficilis has been described and illustrated by Hasegawa (1980) and Piippo (1993). The following description of D. cucullatus is based on the holotype kept in Geneva Herbarium (G) and recently collections from Thailand.